2012
DOI: 10.1590/s0100-06832012000300013
|View full text |Cite
|
Sign up to set email alerts
|

Proposal for an index to classify irrigation water quality: a case study in northeastern Brazil

Abstract: suMMary one way of classifying water quality is by means of indices, in which a series of parameters analyzed are joined a single value, facilitating the interpretation of extensive lists of variables or indicators, underlying the classification of water quality. the objective of this study was to develop a statistically based index to classify water according to the Irrigation Water Quality Index (IWQI), to evaluate the ionic composition of water for use in irrigation and classify it by its source. for this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…In addition, crop yield seems to be lower in soils with high contents of Mg, or when irrigation is conducted using waters with high levels of this element, even when infiltration is adequate. Maia & Rodrigues (2012), proposing a water quality index, reported that yield loss is due to Ca deficiency induced by the excess of exchangeable Mg in the soil. P 1 -First sampling period; P 2 -Second sampling period; P 3 -Third sampling period; P 4 -Fourth sampling period For brackish well water, the indices of the deviations in the indicators remained between 0.05 for Na in P 3 in Jacu and 3.98 for SAR in P 3 in EMA.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, crop yield seems to be lower in soils with high contents of Mg, or when irrigation is conducted using waters with high levels of this element, even when infiltration is adequate. Maia & Rodrigues (2012), proposing a water quality index, reported that yield loss is due to Ca deficiency induced by the excess of exchangeable Mg in the soil. P 1 -First sampling period; P 2 -Second sampling period; P 3 -Third sampling period; P 4 -Fourth sampling period For brackish well water, the indices of the deviations in the indicators remained between 0.05 for Na in P 3 in Jacu and 3.98 for SAR in P 3 in EMA.…”
Section: Resultsmentioning
confidence: 99%
“…[27] record the highest chlorophyll a content in Marzanaland shallow wetland in Iran during warm periods. Depending on irrigated water quality index (IWQI) values for Duhok lake dam in different seasons, water quality is regarded as excellent types for irrigation purpose based on [21] classification (Table 4). Site 3 is characterized by higher values with maximum value 1.72 observed during winter.…”
Section: Resultsmentioning
confidence: 99%
“…Where, WQIi is Water Quality Index for the characteristic and IWQI is Irrigation Water Quality Index. The results, are classified according to [21] Table (1).…”
Section: -mentioning
confidence: 99%
“…Ayers and Westcott (1999) point out that the productivity of most crops is lower in soils with high magnesium contents, or when irrigation water contains high levels of this element, even when the infiltration is adequate. According to Maia and Rodrigues (2012) this is due to calcium deficiency induced by the excess of exchangeable magnesium in the soil. In this situation, the effects of sodium are slightly higher when it is present in the irrigation water, or in the soil solution, since, due to the lower attraction force presented by magnesium, there may be dispersion of the clays, generating problems of infiltration.…”
Section: Brackish Water From Wellsmentioning
confidence: 99%